2004
DOI: 10.3354/meps282193
|View full text |Cite
|
Sign up to set email alerts
|

Life on the edge: do biomechanical and behavioral adaptations to wave-exposure correlate with habitat partitioning in predatory whelks?

Abstract: The rocky littoral is a highly stressed but species rich environment in which adaptive trade-offs underlie the specialization that permits habitat partitioning by closely-related species. Habitat partitioning by prey species is generally attributed to differential tolerances to physiological stresses and competition for resources. Partitioning by predators is, however, less understood and also mainly related to thermal tolerance. We test the hypothesis that differential biomechanical and behavioral adaptations… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
37
0

Year Published

2005
2005
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 37 publications
(38 citation statements)
references
References 52 publications
1
37
0
Order By: Relevance
“…For organisms possessing a simple holdfast (e.g. barnacles or gastropod molluscs), the scaled attachment force correlates with the tenacity, as the size of the adhesive organ is generally proportional to the size of the animal (Grenon & Walker 1981, Rilov et al 2004. This is, however, not necessarily the case for organisms possessing a multi-tethered holdfast (e.g.…”
Section: Introductionmentioning
confidence: 74%
See 1 more Smart Citation
“…For organisms possessing a simple holdfast (e.g. barnacles or gastropod molluscs), the scaled attachment force correlates with the tenacity, as the size of the adhesive organ is generally proportional to the size of the animal (Grenon & Walker 1981, Rilov et al 2004. This is, however, not necessarily the case for organisms possessing a multi-tethered holdfast (e.g.…”
Section: Introductionmentioning
confidence: 74%
“…This is similar to the situation described for whelks, but different from the case of limpets. Rilov et al (2004) studied 2 Mediterranean whelks, Stramonita haemastoma from a wave-exposed habitat and Hexaplex trunculus found only subtidally in more calm littoral environments. The 2 species possess the same tenacity, but the former is less prone to dislodgment by waves due to a more streamlined shell and a larger foot.…”
Section: Interspecific Analysismentioning
confidence: 99%
“…This concept of physical stress affecting the strength of trophic interactions led to some interesting research (e.g. Menge, 1978;Power et al, 1988;Peckarsky et al, 1990;Hart, 1992;Rilov et al, 2004) and has proven to be especially productive in studies of marine rocky intertidal habitats (Menge, 2000). For example, comparison of benthic community dynamics between different flow regimes in a Maine estuary showed that crab predation was most important in low-flow sites, whereas recruitment and particle delivery dominated the high-flow sites (Leonard et al, 1998).…”
Section: Discussionmentioning
confidence: 99%
“…Spatio-temporal variability in the population structure of this species has been attributed to differences in abiotic processes, such as habitat structure and the degree of wave exposure (e.g. Richardson and brown, 1990;Rilov et al, 2001Rilov et al, , 2004brown et al, 2004). Similarly, limited prey availability, in terms of abundance and biomass, has been suggested to be a possible mechanism behind the low abundances and growth rates of these intertidal carnivores on some coasts (mckillup and butler, 1983;burrows and Hughes, 1990;mckillup and mckillup, 1997;ota and Tokeshi, 2000).…”
mentioning
confidence: 99%